The Reproducibility of 4-km Time Trial (TT) Performance Following Individualised Sodium Bicarbonate Supplementation: a Randomised Controlled Trial in Trained Cyclists - Lewis Anthony Gough; Sanjoy Kumar Deb; Andy Sparks; Lars Robert McNaughton (SpringerOpen, 2017)
Abstract Background Individual time to peak blood bicarbonate (HCO3 −) has demonstrated good to excellent reproducibility following ingestion of both 0.2 g kg−1 body mass (BM) and 0.3 g kg−1 BM sodium bicarbonate (NaHCO3), but the consistency of the time trial (TT) performance response using such an individualised NaHCO3 ingestion strategy remains unknown. This study therefore evaluated the reproducibility of 4-km TT performance following NaHCO3 ingestion individualised to time to peak blood bicarbonate. Methods Eleven trained male cyclists completed five randomised treatments with prior ingestion of 0.2 g kg−1 (SBC2) or 0.3 g kg−1 BM (SBC3) NaHCO3, on two separate occasions each, or a control trial entailing no supplementation. Participants completed a 4-km cycling TT on a Velotron ergometer where time to complete, power and speed were measured, whilst acid-base blood parameters were also recorded (pH and blood bicarbonate concentration HCO3 −) and lactate [La−]. Results Alkalosis was achieved prior to exercise in both SBC2 and SBC3, as pH and HCO3 − were greater compared to baseline (p < 0.001), with no differences between treatments (p > 0.05). The reproducibility of the mean absolute change from baseline to peak in HCO3 − was good in SBC2 (r = 0.68) and excellent in SBC3 (r = 0.78). The performance responses following both SBC2 and SBC3 displayed excellent reproducibility (r range = 0.97 to 0.99). Conclusions Results demonstrate excellent reproducibility of exercise performance following individualised NaHCO3 ingestion, which is due to the high reproducibility of blood acid-base variables with repeat administration of NaHCO3. Using a time to peak HCO3 - strategy seems to cause no dose-dependent effects on performance for exercise of this duration and intensity; therefore, athletes may consider smaller doses of NaHCO3 to mitigate gastrointestinal (GI) discomfort.